Answer:
x = 4
Step-by-step explanation:
Simplifying
3x + 15 = 6x + 3
Reorder the terms:
15 + 3x = 6x + 3
Reorder the terms:
15 + 3x = 3 + 6x
Solving
15 + 3x = 3 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
15 + 3x + -6x = 3 + 6x + -6x
Combine like terms: 3x + -6x = -3x
15 + -3x = 3 + 6x + -6x
Combine like terms: 6x + -6x = 0
15 + -3x = 3 + 0
15 + -3x = 3
Add '-15' to each side of the equation.
15 + -15 + -3x = 3 + -15
Combine like terms: 15 + -15 = 0
0 + -3x = 3 + -15
-3x = 3 + -15
Combine like terms: 3 + -15 = -12
-3x = -12
Divide each side by '-3'.
x = 4
Simplifying
x = 4
Answer:
I don't know what inductive reasoning is but, the next two numbers in the pattern are -243 and +729
Step-by-step explanation:
each number is being multiplied by a factor of (-3).
2504, as 2499 is 5 less, yet rounds to 2.5K. It is the highest possible for rounding to the tens, as 2505 rounds to 2510.
Answer:
4x²+x+5.
Step-by-step explanation:
5x²+4x+1-(X²+3x-4).
5x²+4x+1-x²-3x+4.
5x²-x²+4x-3x+1+4.
4x²+x+5.
React to my new music video Dasgasdom3 East Coast junkie